Rapid (FLASH-FLIM) imaging of protoporphyrin IX in a lipid mixture using a CMOS based widefield fluorescence lifetime imaging camera in real time for margin demarcation applications. (11th January 2021) - Sagoo, Kulwinder; Cumberbatch, Nathan; Holland, Adam; Hungerford, Graham
Abstract: The fluorescence from protoporphyrin IX (PpIX) has been employed to characterise cellular activity and assist in the visualisation of tumour cells. Its formation can be induced by 5-aminolevulonic acid (5-ALA) which is metabolised by tumour cells to form PpIX. The PpIX is localised within the cells, rather than spreading into the vascular system. This, plus its photophysics, exhibits potential in photodynamic therapy. Hence its study and the ability to rapidly image its localisation is of importance, especially in the field of fluorescence guided surgery. This has led to investigations using tissue phantoms and widefield intensity imaging. Aggregation or the presence of photoproducts can alter PpIX emission, which has implications using widefield imaging and a broad wavelength range detection. The use of the fluorescence lifetime imaging (FLIM) is therefore advantageous as it can distinguish between the emissive species as they exhibit different fluorescence lifetimes. Here we use PpIX in a construct consisting of lipid mixture (Intralipid), employed to simulate fat content and optical scattering, in a gellan gum matrix. PpIX in intralipid in aqueous solution was injected into the gellan host to form inclusions. The samples are imaged using commercial widefield TCSPC camera based on a sensor chip with 192 × 128 pixels. Each pixel contains both detection and photon timing enabling the Fluorescence Lifetime Acquisition by Simultaneous Histogramming (FLASH). This 'FLASH-FLIM' approach enables widefield fluorescence lifetime images, displayed in real time to be acquired, which has potential for use in visualising tumour boundaries.